Kesiapsiagaan Masyarakat dalam Menghadapi Gempa Bumi (Mengenang 14 Tahun Silam Gempa Bumi Bantul, Yogyakarta) - Nur Hamid (Altruis: Journal of Community Services, 2020)
The earthquake hit Bantul regency, Yogyakarta, has brought life lesson for us that preparedness is urgently demanded to face potential earthquake in the future. This publication aims to discover how is both government and society readiness to act when earthquake strikes on unprecedented times. Method employed was literature study method by conducting in-depth analysis towards literatures related to earthquake disaster in Bantul in the year of 2006. This study revealed that Bantul dwellers have been high alerted to face earthquake. The disaster preparedness covers a range of fields which are on public facility, information system, physics or building, economy, education, society’s capacities enhancement, and religion.